THE INFLUENCE OF EDUCATION, REPORTING BEHAVIOR AND PERCEPTIONS OF ACCOUNTING STANDARDS ON FINANCIAL REPORTING ACCOUNTABILITY IN ISLAMIC BOARDING SCHOOLS - Hendra Raza (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
This research aims to determine the influence of education, reporting behavior and perceptions of accounting standards on the financial reporting accountability of Islamic boarding schools in Lhokseumawe City. The data used in this research is primary data from 76 respondents who are heads of Islamic boarding schools. The sampling technique used is random sampling technique. The method used is the multiple linear regression method. The research results show that education, reporting behavior and perceptions of accounting standards have a positive and significant effect on the financial reporting accountability of Islamic boarding schools in Lhokseumawe City.